Parental Attachment and Psychosocial Adjustment in Adolescents Exposed to Marital Conflict - Jesús Maya; Isabel Fuentes; Ana Isabel Arcos-Romero; Lucía Jiménez (MDPI AG, 2024)
(1) Background: Interparental conflict is a phenomenon that poses a serious threat not only to the quality of life of the couple but also to the father-child relationship, mother-child relationship, and well-being of adolescents. This study examined the difference in parental attachment and adjustment in adolescents exposed to marital conflict versus those not exposed to parental conflicts in low-income areas. (2) Methods: 67 adolescents involved in Child Welfare Services (CWS) in disadvantaged neighbourhoods in southern Spain were examined. The sample was split into two groups according to the exposure to marital conflict. Subsequently, differences between groups were analysed on father attachment, mother attachment, aggression, antisocial behaviour, and emotional intelligence. (3) Results: Primarily, the data showed significantly worse attachment with the father among conflict-exposed versus non-conflict-exposed adolescents. These results were not found for the attachment with the mother. Additionally, greater anger and worse stress management were found in conflict-exposed adolescents. (4) Conclusions: The results partially confirmed the spillover and compensatory hypothesis. Practical implications point out that developing preventive interventions that protect the father-adolescent attachment in situations of family conflict is recommended.